LEGAL SECURITY AND COUP D’ÉTAT – HISTORICAL AND MODERN PERSPECTIVES - Konarski, Marcin (Review of European and Comparative Law, 2017)
The article discusses the relationship between the concepts of “legal security” and “coup d’état” on the basis of the evolution of these concepts over the centuries. The analysis of the terms which the author is interested in, adopted as the subject of this study, leads to the conclusion that, in particular, the concept of “coup d’état” is often mistakenly refereed to as a “revolution” or a “putsch”. A political upheaval, one of the methods of which is a coup d’ état, should be regarded, in the light of the research carried out, as deviating from the concept and character of a social up-heaval. In the case of a political upheaval, the legal security of the individual is usu-ally protected as before, and a possible lack of such security should only be treated as a result of the natural tendency of the individual to protect his or her legal status within a state organisation. It is only with changes of social (class) character, which may be an indirect consequence of a political upheaval, that the addresses of legal norms may have justified concerns about their legal safety.